A case of bullous morphea - Qiang HU; Jianmin CHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
A 69-year-old man presented with a firm plaque on the back for one year. Physical examination revealed a coin-sized red scaly plaque on the back with atrophic center and elevated borders. Bleeding and crusts were visible. Histopathology showed epidermal atrophy, formation of subepidermal blister, superficial dermal edema and increased amount and density of collagen fibers in the dermis. Infiltration of inflammatory cells was observed between collagen fiber bundles and perivessels. The diagnosis was bullous morphea. The skin lesion was improved after 3-month treatments with compound glycyrrhizin tablets and 1% pimecrolimus cream.